TEACHER PERSPECTIVES ON STRATEGIES TO ENHANCE ENGLISH SPEAKING PROFICIENCY IN EFL CLASSROOMS - Lailatun Najmiah; Pajrian Noor; Muhammad Fauzi (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This research explores English as a Foreign Language (EFL) teachers' perspectives on strategies to improve students' speaking proficiency in classroom settings. The study specifically examines the approaches used by EFL teachers to enhance speaking skills and the challenges faced in EFL classrooms. A qualitative descriptive approach was adopted, focusing on two experienced EFL teachers from a rural senior high school in South Kalimantan. Data were collected through semi-structured interviews and classroom observations. The results reveal that task-based learning, role-play, and project-based learning are commonly used strategies. However, challenges such as student reluctance, limited class time, and lack of resources persist. The study emphasizes the importance of teacher adaptability and a balanced approach to speaking instruction, while still using traditional tools to maximize student engagement.